Entitativity of Concurrent Sponsors: Implications for Properties and Sponsors. Issue 3 (3rd July 2018) - Dickenson, Peter; Souchon, Anne L.
Abstract : We examine concurrent sponsors' entitativity as a driver of people's intentions to view the sponsored property and ultimately their intentions to purchase from a concurrent sponsor. Entitativity is the degree to which audiences perceive a collective as a group. We consider moderators to the relationship between entitativity and viewing intentions within two sponsorship contexts, namely, sponsors investing financial versus nonfinancial resources in properties. We use factorial survey designs and structural equation modeling (SEM) to test the model across two studies. The results are consistent. Entitativity is positively related to the likelihood of viewing a sponsored property, and viewing intention is positively related to purchase intention. The entitativity–viewing intention relationship is moderated by sponsor sincerity in the context of sponsors investing products/services but not sponsors investing financial resources. Findings are discussed, and avenues for further research drawn.